Dementia Diagnosis Disparities by Race and Ethnicity. Issue 8 (August 2021) - Lin, Pei-Jung; Daly, Allan T.; Olchanski, Natalia; Cohen, Joshua T.; Neumann, Peter J.; Faul, Jessica D.; Fillit, Howard M.; Freund, Karen M.
Abstract : Background: Dementia is often underdiagnosed and this problem is more common among some ethnoracial groups. Objective: The objective of this study was to examine racial and ethnic disparities in the timeliness of receiving a clinical diagnosis of dementia. Research Design: This was a prospective cohort study. Subjects: A total of 3966 participants age 70 years and above with probable dementia in the Health and Retirement Study, linked with their Medicare and Medicaid claims. Measures: We performed logistic regression to compare the likelihood of having a missed or delayed dementia diagnosis in claims by race/ethnicity. We analyzed dementia severity, measured by cognition and daily function, at the time of a dementia diagnosis documented in claims, and estimated average dementia diagnosis delay, by race/ethnicity. Results: A higher proportion of non-Hispanic Blacks and Hispanics had a missed/delayed clinical dementia diagnosis compared with non-Hispanic Whites (46% and 54% vs. 41%, P <0.001). Fully adjusted logistic regression results suggested more frequent missed/delayed dementia diagnoses among non-Hispanic Blacks (odds ratio=1.12; 95% confidence interval: 0.91–1.38) and Hispanics (odds ratio=1.58; 95% confidence interval: 1.20–2.07). Non-Hispanic Blacks and Hispanics had a poorer cognitive function and more functional limitations than non-Hispanic Whites around the time of receiving a claims-based dementia diagnosis. The estimated mean diagnosis delay was 34.6 months for non-Hispanic Blacks and 43.8 months for Hispanics, compared with 31.2 months for non-Hispanic Whites. Conclusions: Non-Hispanic Blacks and Hispanics may experience a missed or delayed diagnosis of dementia more often and have longer diagnosis delays. When diagnosed, non-Hispanic Blacks and Hispanics may have more advanced dementia. Public health efforts should prioritize racial and ethnic underrepresented communities when promoting early diagnosis of dementia. Abstract : Supplemental Digital Content is available in the text.